Constructing imine groups on the surface of Cu1/Pd(111) as a novel strategy for CO2 hydrogenation to methanol. Issue 15 (21st March 2023) - Wang, Sanmei; Li, Qi; Xin, Yue; Hu, Sunpei; Guo, Xiaoxi; Zhang, Yong; Zhang, Ling; Chen, Bingang; Zhang, Wenhua; Wang, Liangbing
Abstract : Developing a promising strategy to improve the limited selectivity and activity of traditional Pd–Cu bimetallic catalysts for CO2 hydrogenation to methanol (CH3 OH) remains a grand challenge. Abstract : Developing a promising strategy to improve the limited selectivity and activity of traditional Pd–Cu bimetallic catalysts for CO2 hydrogenation to methanol (CH3 OH) remains a grand challenge. By using density functional theory calculations, we discovered that introducing imine groups on the Cu1 /Pd(111) surface through a condensation reaction of aldehydes and amines is an intriguing approach for simultaneously enhancing the selectivity and activity of Cu1 /Pd(111) for CO2 hydrogenation to CH3 OH. The imine groups formed by amino reactions with acrolein on the Cu1 /Pd(111) surface (C3 H4 O@NH2 -Cu1 /Pd(111)) improved the turnover frequency (TOF). The imine group optimized the electronic structure of active sites and increased electron transfer to the anti-bonding orbital of CO2, facilitating the activity of C3 H4 O@NH2 -Cu1 /Pd(111) for CO2 hydrogenation to CH3 OH. Besides, the inhibition of CO by-products and the low desorption energy of CH3 OH were responsible for the high selectivity of C3 H4 O@NH2 -Cu1 /Pd(111) for CH3 OH. This work advances our understanding of the role of imines in catalysis and provides a new strategy for designing excellent functional group-modified catalysts for the hydrogenation of CO2 to CH3 OH.